From Aimless Stray To Charting The Way: Financing Policy Reforms To Bolster Indonesia’s Downstreaming Strategy - Lahadalia, Bahlil; Wijaya, Chandra; Subroto, Athor (Universitas Muhammadiyah Malang, 2024)
Purpose: A major impediment to the entry of domestic firms into these sectors is limited access to financing. This study seeks to analyze the constraints to financing access in Indonesia and to formulate policy recommendations to address them by employing an integrative literature review and comparative analysis of East Asian countries. Methodology/approach: This paper employs an integrative literature review and comparative analysis to explore potential policy solutions for mobilizing capital for Indonesia’s downstream industry. Findings: Findings indicate that Indonesia’s financial system, following substantial liberalization, now tends to favor projects with short-term returns over long-term downstream manufacturing projects that are critical for economic transformation. Practical implications: Indonesia must direct its limited capital towards strategic downstream investments. The paper suggests three policy options: 1) providing direct preferential loans; 2) offering guarantees; and 3) injecting equity into targeted domestic firms. Originality/value: The recommendations come with several caveats, including robust governance, specific conditionalities, and stringent evaluation to ensure that financial support targets the most competitive enterprises that can meet the government’s long-term development goals. This research found that while the government's proactive financing presents inherent risk, the greater peril lies in inaction, which could further consign Indonesia to the middle-income trap.